Simultaneous interface application development for an electrometer and a source meter using LabVIEW to study three terminals semiconducting device - Ratul, Mahadi Hassan (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2018.